Penginjilan yang Sesungguhnya: Siapa saja yang Harus Berperan? - Eben Munthe (Sekolah Tinggi Alkitab Penyebaran Injil Majalengka, 2020)
There are Christians who feel that they can choose (separate), between the gospel message and social service (struggle for equal rights, peace, love, struggle against injustice, oppression and indifference, poverty, hunger, ignorance, economy, politics, liberated oppressed). Some people say: